2008
DOI: 10.2319/100207-474.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short- and Long-Term Celecoxib on Orthodontic Tooth Movement

Abstract: Objective: To test the hypothesis that short-and long-term celecoxib administration has no effect on orthodontic tooth movement. Materials and Methods: Male Wistar rats were submitted to short-(3 days) and long-term (14 days) celecoxib administration, while the respective control groups received equivolumetric saline intraperitoneal injections. The upper left first molars of all rats were moved mesially for 14 days by a fixed orthodontic appliance exerting 50 g force upon insertion. After the experimental peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 37 publications
0
30
0
4
Order By: Relevance
“…[23] Long-term effect of celecoxib has shown to reduce the rate of orthodontic tooth movement. [26] Acetaminophen is still the drug of choice for treating the discomfort of tooth movement because no advantages are derived from the use of new COX2 inhibiting drugs. [27]…”
mentioning
confidence: 99%
“…[23] Long-term effect of celecoxib has shown to reduce the rate of orthodontic tooth movement. [26] Acetaminophen is still the drug of choice for treating the discomfort of tooth movement because no advantages are derived from the use of new COX2 inhibiting drugs. [27]…”
mentioning
confidence: 99%
“…The present review shows that paracetamol (acetaminophen) was the only drug that presented unanimous results regarding the influence on orthodontic movement. All studies showed that this drug did not interfere within tooth movement throughout the entire experimental period (Arias and Marquez-Orozco 2006, Hauber Gameiro et al 2008, Gonzales et al 2009). These aspects strengthen the hypothesis that paracetamol does not exert intense activity regarding the inhibition of peripheral synthesis of prostaglandins, reducing the pain by acting along the central nervous system (Arias and Marquez-Orozco 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, these drugs showed distinct effects regarding orthodontic movement, either having negative influence on it or not interfering with it. However, celecoxib responds more frequently for tooth displacement inhibition, exerting distinct levels of interference in three studies (De Carlos et al 2007, Hauber Gameiro et al 2008, Stabile et al 2009). The distinct effects obtained with the use of these drugs may be related to some factors: the half-life of the drug, the bioavailability, the form of administration, the concentration, the experimental period, and the methods of assessing tooth movement (De Carlos et al 2006, Hauber Gameiro et al 2008.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations